Some Hygienic Aspects of Risk and Prevention of Occupational Respiratory Diseases in Animal Workers - Kasimov, Kh.O.; Ibrokhimov, K.I. (International Journal of Membrane Science and Technology, 2023)
The article examines the main occupational risk factors for the development of respiratory diseases in livestock workers (cattle breeding, pig farming), analyzes the dynamics and structure of occupational morbidity, scientifically substantiates the hygienic principles of managing occupational health risks for this category of workers and recommendations for primary and secondary prevention of occupational respiratory diseases.